Respostas
respondido por:
0
Olá Graziela
(tg(75) - 1)/(1 + tg(75))
tg(75) = 2 + √3
(2 + √3 - 1)/(1 + 2 + √3) = (1 + √3)/(3 + √3)
(1 + √3)*(3 - √3)/((3 + √3)*(3 - √3) =
(3 + 3√3 - √3 - 3)/(9 - 3) = 2√3/6 = √3/3
(tg(75) - 1)/(1 + tg(75))
tg(75) = 2 + √3
(2 + √3 - 1)/(1 + 2 + √3) = (1 + √3)/(3 + √3)
(1 + √3)*(3 - √3)/((3 + √3)*(3 - √3) =
(3 + 3√3 - √3 - 3)/(9 - 3) = 2√3/6 = √3/3
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás